A STUDY ON WORK LIFE BALANCE OF WOMEN PROFESSORS WORKING IN SELECTED COLLEGES IN CHENNAI CITY - R. DIVYA; Dr. R. IYAPPAN (The Bioscan, 2026)
The time period Work Life Balance used to be first coined in 1986. It does now not imply equal stability however is of attempting to time table an equal wide variety of hours for every of a number of work and non-public activities.